2021
DOI: 10.3390/su13116363
|View full text |Cite
|
Sign up to set email alerts
|

The Higher Education Sustainability before and during the COVID-19 Pandemic: A Spanish and Ecuadorian Case

Abstract: Information and communication technologies (ICTs) are key to create sustainable higher education institutions (HEIs). Most researchers focused on the students’ perspective, especially during the online teaching caused by COVID-19; however, university teachers are often forgotten, having their opinion missing. This study’s objective was to determine the factors that contribute to the inclusion of ICTs. The research based on a comparative study through an online qualitative survey focused on the inclusion and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Furthermore, current research sheds light on the dimension of sustainability in the context of the pandemic. Studies on sustainability education [27,28] as well as on sustainable online learning and teaching [29][30][31] have highlighted challenges and possibilities for sustainable development in the context of the pandemic. Especially social distancing and temporary lockdowns are reported to have a significant impact on the everyday life and education of millions of students.…”
Section: Effects Of the Covid-19 Pandemic On The Spatiality Of University Students' Education And Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, current research sheds light on the dimension of sustainability in the context of the pandemic. Studies on sustainability education [27,28] as well as on sustainable online learning and teaching [29][30][31] have highlighted challenges and possibilities for sustainable development in the context of the pandemic. Especially social distancing and temporary lockdowns are reported to have a significant impact on the everyday life and education of millions of students.…”
Section: Effects Of the Covid-19 Pandemic On The Spatiality Of University Students' Education And Learningmentioning
confidence: 99%
“…Based on our extensive study, we see the implementation of the following medium-term measures as essential to make teaching future-proof and distance learning more learnercentered and sustainable beyond the phase of the pandemic [62]: the continuation of the digitization of university processes, literature, and library services must be strongly fostered. Based on this study, the retention of online course offerings, the establishment of hybrid courses, and the strong encouragement of creative and innovative online and blended teaching methods are recommended [27]. Current distance learning formats should not be adopted unchanged, but prevailing problems should be removed, such as the lack of social contacts and time structure.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Both formal presentations and independent teaching methodologies are necessary, and teaching methodologies that promote them should therefore be implemented in engineering courses. Different studies have shown the validity for students’ learning of, for instance, project-based learning or cooperative work, which can replace the traditional classes performed for the resolution of exercises [ 5 , 41 , 50 ].…”
Section: Overall Discussionmentioning
confidence: 99%
“…They allow collaboration in groups to conduct experiments [75], while avoiding, at the same time, the health risks. The COVID-19 pandemic not only increased substantially the degree of implementation and use of VLs in educational institutions but also significantly improved the perception of the teaching staff about their utility [11,12,14,32,67]. Several authors consider that virtual laboratories will continue to be a constant presence in the post-COVID educational landscape, coexisting with physical laboratories [12,67,76].…”
Section: Introductionmentioning
confidence: 99%